Message from the Director General 2011 = Mensaje del Director General 2011 - Echeverría, Rubén G. (International Center for Tropical Agriculture, 2010)
CIAT began to implement new strategic directions during 2009, taking into account major reforms in the CGIAR, or Consultative Group on International Agricultural Research, and focusing on global challenges, particularly climate change, food security, and poverty. Our scientists, working with partners, will help confront these challenges by applying in practical ways the concept of eco-efficient agriculture. This is an agriculture that (1) uses resources more effectively to achieve sustainable increases in productivity, (2) reduces the degradation of natural resources, and (3) creates opportunities for boosting incomes and employment in rural areas.